Analysis to the Experiment of Green Pepper Transport with Mechanically Refrigerated Car - 罗荣武; 谢如鹤 (Zhileng xuebao)
By tracing experiment,we review the long distance transportation of green pepper with railway mechanically refrigerated car.This paper analyzes the change of temperature theoretically and experimentally,organization and quality in transport experiment,and put forward some suggestions for improving transport methods and quality.